Assessing the Adequacy of Small Solute Clearance for Various Dialysis Modalities, with Inclusion of Residual Native Kidney Function. Issue 3 (14th February 2017) - Chin, Andrew I.; Depner, Thomas A.; Daugirdas, John T.
Abstract: Measurement of small molecule clearance remains important in the clinical care of patients requiring long‐term dialysis. Many patients maintain a significant degree of residual native kidney function and may have nontraditional schedules with or without combined dialysis modalities. In this review, we examine and outline methods for comparing small molecule clearances among various dialysis prescriptions and modalities, with inclusion of residual kidney urea clearance.